Exploring the possibilities to control the molecular switching properties and dynamics: A field-switchable rotor-stator molecular system - Petreska, Irina; Pejov, Ljupco; Kocarev, Ljupco (AIP Publishing, 2011)
A bistable, dipolar stator-rotor molecular system-candidate for molecular electronics is investigated. We demonstrate that it is possible to control the intramolecular torsional states and dynamics in this system by applying an appropriate additional electric field (instead of biasing one), achieving fine tuning and modulation of the relevant properties. The electric field effects on the quantities responsible for torsional dynamics (potential energy surface, potential barrier height, quantum and classical transition probabilities, correlation time, HOMO-LUMO gap) are studied from first principles. Our results indicate that it is possible to artificially stabilize the metastable conformational state of the studied molecule. The importance of this is evident, as the current-voltage characteristics of the metastable state are clearly distinguishable from the current-voltage characteristics of the two stable states. We report for the first time exact calculations related to the possibilities to control the thermally induced stochastic switching, and reduce the noise in a practical application. Thus, we believe that the molecule studied in this paper could operate as a field-switchable molecular device under real conditions.